In Vitro Cytotoxicity and In Vivo Antimammary Tumor Effects of the Hydroethanolic Extract of Acacia seyal (Mimosaceae) Stem Bark. (25th March 2018) - Zingue, Stephane; Njuh, Amstrong Nang; Tueche, Alain Brice; Tamsa, Jeremie; Tchoupang, Edwige Nana; Kakene, Stanislas Djaouli; Sipping, Marius Trésor Kemegne; Njamen, Dieudonné
Abstract : The present study was designed to evaluate the in vitro and in vivo antitumor effects of A. seyal hydroethanolic extract on breast cancer. The cytotoxicity of A. seyal extract was evaluated using resazurin reduction assay in 9 cell lines. Further, the protective effect of the hydroethanolic extract of A. seyal stem barks was evaluated on 7, 12-dimethylbenz(a)anthracene- (DMBA-) induced breast cancer rat model. Incidence, burden, volume, and histological analysis of mammary tumors were measured. The Acacia seyal extract exhibited CC50 of 100 in MCF-7 cells after 24 h. In vivo, no tumors were detected in rats from the control group, while 11 rats out of 12 (91.66%) developed mammary tumors in the DMBA-exposed group receiving only the vehicle. Acacia seyal extract significantly (p < 0.01 ) and in the dose-dependent manner reduced tumor incidence (3 rats out of 12 at the dose of 300 mg/kg), burden [62.1% (150 mg/kg) and 65.8% (300 mg/kg)], and mass. It protected rats against DMBA-induced breast hyperplasia, with an optimal effect at the dose of 300 mg/kg. Taken altogether, these results suggest that the hydroethanolic extract of Acacia seyal might contain phytoconstituents endowed with antitumoral properties, which could protect against the breast cancer induced in rats.